A novel catalytic route for hydrogenation–dehydrogenation of 2LiH + MgB2via in situ formed core–shell LixTiO2 nanoparticles. Issue 25 (7th June 2017) - Puszkiel, J. A.; Castro Riglos, M. V.; Ramallo-López, J. M.; Mizrahi, M.; Karimi, F.; Santoru, A.; Hoell, A.; Gennari, F. C.; Larochette, P. Arneodo; Pistidda, C.; Klassen, T.; Bellosta von Colbe, J. M.; et al.
Abstract : Aiming to improve the hydrogen storage properties of 2LiH + MgB2 (Li-RHC), the effect of the in situ formed and low cost Li x TiO2 is investigated. Abstract : Aiming to improve the hydrogen storage properties of 2LiH + MgB2 (Li-RHC), the effect of TiO2 addition to Li-RHC is investigated. The presence of TiO2 leads to the in situ formation of core–shell Li x TiO2 nanoparticles during milling and upon heating. These nanoparticles markedly enhance the hydrogen storage properties of Li-RHC. Throughout hydrogenation–dehydrogenation cycling at 400 °C a 1 mol% TiO2 doped Li-RHC material shows sustainable hydrogen capacity of ∼10 wt% and short hydrogenation and dehydrogenation times of just 25 and 50 minutes, respectively. The in situ formed core–shell Li x TiO2 nanoparticles confer proper microstructural refinement to the Li-RHC, thus preventing the material's agglomeration upon cycling. An analysis of the kinetic mechanisms shows that the presence of the core–shell Li x TiO2 nanoparticles accelerates the one-dimensional interface-controlled mechanism during hydrogenation owing to the high Li + mobility through the Li x TiO2 lattice. Upon dehydrogenation, the in situ formed core–shell Li x TiO2 nanoparticles do not modify the dehydrogenation thermodynamic properties of the Li-RHC itself. A new approach by the combination of two kinetic models evidences that the activation energy of both MgH2 decomposition and MgB2 formation is reduced. These improvements are due to a novel catalytic mechanism via Li + source/sink reversible reactions.